The Causal Impact of Gender Norms on Mothers' Employment Attitudes and Expectations - Henning Hermes; Marina Krauß; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (CESifo GmbH, 2024)
This field experiment investigates the causal impact of mothers' perceptions of gender norms on their employment attitudes and labor-supply expectations. We provide mothers of young children in Germany with information about the prevailing gender norm regarding maternal employment in their city. At baseline, over 70% of mothers incorrectly perceive this gender norm as too conservative. Our randomized treatment improves the accuracy of these perceptions, significantly reducing the share of mothers who misperceive gender norms as overly conservative. The treatment also shifts mothers' own labor-market attitudes towards being more liberal—and we show that specifically the shifted attitude is a strong predictor of mothers' future labor-market participation. Consistently, treated mothers are significantly more likely to plan an increase in their working hours one year ahead.
Keywords: J16; J18; J22; C93; 330; gender norms; maternal employment; gender equality; randomized controlled trial